Ultra-fast in-situ X-ray studies of evolving columnar dendrites in solidifying steel weld pools. Issue 1 (May 2015) - Mirihanage, W U; Di Michiel, M; Mathiesen, R H
Abstract: High-brilliance polychromatic synchrotron radiation has been used to conduct in-situ studies of the solidification microstructure evolution during simulated welding. The welding simulations were realized by rapidly fusing ∼ 5 mm spot in Fe-Cr-Ni steel. During the solid- liquid-solid phase transformations, a section of the weld pool was placed in an incident 50-150 keV polychromatic synchrotron X-ray beam, in a near-horizontal position at a very low inclination angle. Multiple high-resolution 2D detectors with very high frame rates were utilized to capture time resolved X-ray diffraction data from suitably oriented solid dendrites evolving in the weld pool. Comprehensive analysis of the diffraction data revealed individual and overall dendritic growth characteristics and relevant melt and solid flow dynamics during weld pool solidification, which was completed within 1.5 s. Columnar dendrite tip velocities were estimated from the experimental data and during early stages of solidification were exceeded 4 mm/s. The most remarkable observation revealed through the time-resolved reciprocal space observations are correlated to significant tilting of columnar type dendrites at their root during solidification, presumably caused by convective currents in the weld pool. When the columnar dendrite tilting are transformed to respective metric linear tilting velocities at the dendrite tip; tilting velocities are found to be in the same order of magnitude as the columnar tip growth velocities, suggesting a highly transient nature of growth conditions.